Sharia financial planning assistance to improve community welfare - Novianto, Abdullah Syakur; Amin, Muh. Sirojuddin; Saputri, Laila Sandri; Cinta, Aura; Lestari, Via; Riski, Kumajaya Novi; Kamilah, Saosan; Ambarsari, Emmy; Fariani, Fariani; Lativa, Rachmah Nur; Artamefia, Rachel Amanda Vinka; Febriyani, Nurlatifa; Utami, Merly Violita (Community Empowerment, 2025)
Financial literacy remains a major challenge in Banjarejo Village, significantly impacting the way the community manages their finances. Residents’ understanding of formal financial services remains low. This situation encourages some residents to choose non-formal financial institutions, such as those that are easier to access but carry high interest rates. This community service activity was carried out at the Banjarejo Village Hall, Pakis District, Malang Regency, involving 30 members of the PKK (family welfare movement). The objective of this activity was to increase the community’s understanding of financial literacy and planning. The method used in this activity was direct outreach and counseling for the Banjarejo Village community. The series of community service activities included initial observation, outreach, counseling, and monitoring and evaluation processes. From this activity, the results obtained were that 75% of participants had sufficient understanding and 25% of participants had a high level of understanding of simple financial reporting so that it would affect the financial flow of families and businesses.